PANDEMI COVID-19: FORCE MAJEURE DAN HARDSHIP PADA PERJANJIAN KERJA - Widiastiani, Nindry Sulistya (UI Scholars Hub, 2021)
In the civil law system, there are force majeure and hardship concepts which is related with situation when debtors unable to fulfill their contract obligations. Covid-19 pandemic in Indonesia causes employers’ difficulties in order to fulfill their work agreement obligations, such as payingtheir workers wages and Religious Holiday Allowances. In the context of fulfilling work agreement obligations, force majeure dan hardship concepts could not be found in the Indonesia’s Manpower Law. This conceptual article aims to analyse the chance of using force majeure and hardship concepts in the implementation of work agreement during covid-19 pandemic. The analysis uses conceptual approach to deduce a result. The result shows that covid-19 pandemic could be used as the ground to implement force majeure and hardship concepts if the employers (as debtors) unable to fulfill their obligation from work agreement, such as as paying their workers wages and Religious Holiday Allowances. However, the application of force majeure and hardship concepts are subjective and could not be used as general principles.